Urban mobilities in Mumbai: Towards worker-centric platformisation beyond `urban solutionism' - Tobias Kuttler (Urban Studies, 2024)
As digital mobility platforms, such as ride-hailing apps, have become more widespread and popular, they have garnered public and scholarly interest as potential solutions to challenges of climate change, insufficient mobility services, urban congestion and pollution. This paper examines the potential of ride-hailing platforms through a more critical lens. Thereby I draw attention to how platform transportation workers in Mumbai, India, produce mobility services by collaboratively linking the social and material resources of the city. Networks and communities of transport workers have long been essential for providing intermediate mobility services in Mumbai, and continue to do so in the platform era. Building on these observations, I inquire whether there is potential for the creation of worker-centric platform models that benefit both the workers and the larger urban majority. Therefore, drawing on my fieldwork in Mumbai, I first explore how the current model of digital mobility platforms in Mumbai reinforces socio-spatial fragmentation in Mumbai while leaving workers with decreasing earnings and rising work pressure. Considering the agency of platform workers, I then aim to uncover how platform workers appropriate platform mechanisms and engage their collective knowledge and experiences in order to improve their working situation. I draw upon these insights to highlight how worker-centric approaches to digital mobility platforms can contribute to more inclusive and sustainable cities.
Keywords: 300; alternative platform models; embeddedness; platform mobilities; platform urbanism; South Asia